2022
DOI: 10.1186/s40462-022-00352-3
|View full text |Cite
|
Sign up to set email alerts
|

Across the deserts and sea: inter-individual variation in migration routes of south-central European barn swallows (Hirundo rustica)

Abstract: Background The spatiotemporal organization of migratory routes of long-distance migrants results from trade-offs between minimizing the journey length and en route risk of migration-related mortality, which may be reduced by avoiding crossing inhospitable ecological barriers. Despite flourishing avian migration research in recent decades, little is still known about inter-individual variability in migratory routes, as well as the carry-over effects of spatial and temporal features of migration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…Crossing ecological barriers is one of the most energy-demanding and risky stages in bird migration [43]. Previous studies have found that Barn Swallow populations in Italy and Switzerland typically follow a "clockwise loop migration" pattern, crossing barriers through the central Mediterranean and the Sahara Desert during autumn migration, but shifting to a more western, longer route during spring migration, bypassing the barriers [44]. This study found that the migratory pattern of the breeding population of Barn Swallows in Zhanjiang exhibited a contrary "counter-clockwise loop migration" pattern, with the majority of individuals choosing a western route bypassing the South China Sea to reach the wintering grounds via Vietnam during autumn migration, while during spring migration, they directly crossed the South China Sea, taking a shorter route.…”
Section: Ecological Barriers and Migration Decisionsmentioning
confidence: 99%
“…Crossing ecological barriers is one of the most energy-demanding and risky stages in bird migration [43]. Previous studies have found that Barn Swallow populations in Italy and Switzerland typically follow a "clockwise loop migration" pattern, crossing barriers through the central Mediterranean and the Sahara Desert during autumn migration, but shifting to a more western, longer route during spring migration, bypassing the barriers [44]. This study found that the migratory pattern of the breeding population of Barn Swallows in Zhanjiang exhibited a contrary "counter-clockwise loop migration" pattern, with the majority of individuals choosing a western route bypassing the South China Sea to reach the wintering grounds via Vietnam during autumn migration, while during spring migration, they directly crossed the South China Sea, taking a shorter route.…”
Section: Ecological Barriers and Migration Decisionsmentioning
confidence: 99%
“…The barn swallow is a small migratory passerine bird whose breeding range encompasses the whole Holarctic region. Italian populations spend the non-breeding period mostly in west-African sub-Saharan countries [44,45]. This species breeds synanthropically in rural buildings and forages on aerial insects captured within 500 m of the breeding sites [43].…”
Section: Study Speciesmentioning
confidence: 99%
“…The locations, size, connectivity, and activities of mega-urbanized areas have spread to influence every ecosystem, to the point that One Health for One Planet initiatives require urgent implementation (Barroso et al 2023 ; Fastré et al 2021 ; Yin et al 2022 ). For example, migratory birds must cross these altered biomes to complete their biological cycles and their survival depends on their relationships with ecosystems under pressure (Pancerasa et al 2022 ). Indeed, ecosystems, agrosystems, and mega-urbanizations are now so entangled that the significant flow of materials and organisms between them creates widespread disturbances, such as changes in pollutants, diseases, or predation rates (Krauze and Wagner 2019 ).…”
Section: Introductionmentioning
confidence: 99%